Effect of mercury on growth and pigment content of Cyanobacteria: Westiellopsis prolifica Janet - Nirmal Kumar; Bhavsar Khushboo; Rita Kumar (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Today chemicals are widely used and may enter an aquatic ecosystem which causes an adverse effect on non-target organisms. These are particularly of concern due to increase in annual use of these chemicals worldwide. The present study was carried out to find out the effect of different concentration (2, 4, 6 and 8 ppm) of mercury (Hg) on the growth and photosynthetic pigments of a cynaobacterial species, Westiellopsis prolifica Janet. Experimental observations revealed a gradual growth reduction and the retardation of chlorophyll-a, b and c content with increase in concentrations of Hg+2 with the progressing time period progressed. Also, a fall in carotenoids and phycobillins content of W. prolifica was recorded at the end of incubation time. The results concluded that the Cyanobacterial species have been considered as candidates for use in bioremediation processes due to their potential of Bioaccumulation and Biosorption of heavy metals. But, proper studies are necessary for their practical use.